DECONSTRUCTION OF SIGNS IN THE SPIRITED AWAY ANIME: EXPLORING THE SEMIOTICS OF UMBERTO ECO BY HAYAO MIYAZAKI: DEKONSTRUKSI TANDA DALAM ANIME SPIRITED AWAY: MENELUSURI SEMIOTIKA UMBERTO ECO DALAM KARYA HAYAO MIYAZAKI - Fairuz Fairuz; Muhammad Naufal Hilmy; Nisvisya Maharani; Alya Revani; Puput Rizki; Belia Mala Sari (Jurnal Kata, 2024)
"Spirited Away" is an anime by Hayao Miyazaki produced by Studio Ghibli. This anime is packaged with neat visuals and messages with a rich fantasy narrative and symbolism that reflects culture, values ​​and social criticism. This research explores the signs and hidden meanings in the anime "Spirited Away" which is studied using Umberto Eco's semiotic approach. Analysis includes visual signs, visual symbols, linguistic signs which examine the use of language to reveal its role in building meaning as well as analysis of narrative signs. The method used is a qualitative descriptive method. The data analyzed in the form of sentences, objects and gestures. The results of the research show that the character Chihiro is interpreted as a representation of the transition process from adolescence to adulthood. Loss of identity and fear in a new world are interpreted as symbols of teenagers' fear and uncertainty in facing the future. The anime's unique setting, with a combination of the real world and the magical world, is an interesting sign. The magical world presented in the film, with its various rules and fantastic characters, can be interpreted as a reflection of human social and cultural reality. The real world represented by Chihiro's human world can be interpreted as a symbol of a reality full of challenges and pressure.